IMPLEMENTATION BSPS PROGRAM POLICIES POVERTY REDUCTION TIBAWA DISTRICT - Yunus Dunggio; ANIS NAKI; KARLINA NAPU (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The aims of this study are: 1) to identify and analyze the implementation of bsps program policies in poverty alleviation in tibawa district; 2) to find out what are the factors that determine the success of implementing the bsps program policy in poverty alleviation in tibawa district This study uses a research conducted using a qualitative approach while the type of research used in this thesis research is qualitative descriptive research. The results of this study indicate that: 1) the implementation of the bsps program policy in poverty reduction in tibawa district has not run optimally. In measuring the success of the implementation of the bsps policy, it can be seen from 3 indicators, namely: a) it is seen that the planning has been carried out optimally; b) the implementation of the bsps program has been running but is not yet optimal. One of the non-optimal programs of this bsps is the absence of a clear soup. In addition, the availability of materials also affects the implementation of the bsps program. The availability of materials provided by suppliers or material stores is limited or does not match the demand for goods needed by the recipient community of the bsps program. In addition, the price of materials that are suddenly expensive so that they are not in accordance with the drpb and rab that have been made by the recipients of the bsps program; c) judging from the supervision process has been carried out properly. Supervision is carried out in a preventive and repressive manner. Preventive supervision is carried out before the start of an activity or before the occurrence of financial expenditures for bsps assistance. Meanwhile, repressive supervision is carried out by evaluating financial and operational accountability report documents. This inadequacy can be seen from the fact that there are still some people who do not fully understand and utilize the bsps assistance funds according to their designation; 2) the factors that determine the implementation of the bsps program policy in poverty reduction in tibawa district consist of resources, communication, and disposition